Iranian Exceptionalism and Its Effects on Tehran’s Foreign Relations - Saeed Shokoohi (رهیافتهای سیاسی و بین المللی)
Iran is a unique actor with specific behaviors in the international system. The paper's main question is what are the main elements of Iranian exceptionalism and what are its effects on Iran’s foreign relations? To answer the question, mixed methodology, a combination of interpretive method and directed qualitative content analysis, has been utilized to interpret Iran's outstanding political and thought figures throughout history. Besides, a conceptual framework has been adopted based on the late Morteza Motahari’s viewpoint on Worldview. The findings of the paper demonstrate that crucial principles of Iranian Exceptionalism are: the “Centrality of Iran in the World”, “Representing the God on earth”, “Ideal king/leader idea”, and “‌Believing in the eternal triumph of the Good (Iran) against the Evil (Its enemies)”, “Necessity of Empowerment”, and “ Heavenly mission to lead other nations”. These specific characteristics, combined together, turn International relations realms into a scene of sacred political actions, in which Iran has the mission and transcendental duty to fight the Evils, till the final triumph. What mainstream theories find odd and somehow irrational Iranian behavior, is completely rational, understandable, and predictable via this conceptual framework.